Pertanggungjawaban Pidana Pemimpin Negara Akibat Kejahatan HAM Berat dan Yurisdiksi International Criminal Court - Ar Rafii, Muhammad; Nurfaedah, Nadira Syawaliyah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The aim of this research is to understand the concept of handling carried out by the International Criminal Court, especially through the establishment of a Hybrid Court for serious human rights crimes committed by state leaders and also to understand the concept of accountability for state leaders who have immunity related to serious human rights crimes within the jurisdiction of the International Criminal Court. This research uses a normative juridical method where in the process it examines research from literature study materials and legal provisions, in this case the Rome Statute. Criminal liability of state leaders is a form of international legal instrument used to enforce accountability for international crimes committed by state leaders. International crime is something that has been happening for a long time. Various international crimes committed by state leaders have been in the spotlight of history because of the atrocities committed by the leaders of a state. This research will examine the responsibility of state leaders for serious human rights crimes committed by Liberian President Charles Taylor based on the jurisdiction of the International Criminal Court through the establishment of a hybrid court.